Cob Flies, Megaselia spp. (Diptera: Phoridae), in Sweet Corn - David Owens; Gregg S. Nuessly; Robert Beiriger; Nicholas Larsen (EDIS, 2016)
Phorid flies (Diptera), also known as humpback flies or scuttle flies for their appearance and behavior, are an extremely diverse group of flies that are saprophagous (feed on decaying organic matter), parasitic, or phytophagous (feed on plants). Within the Phoridae family, the genus Megaselia is also extremely diverse, with more than 1400 described species, many very similar in appearance. The name “cob fly” was given to a Megaselia spp. that attacked corn in Texas. This 5-page fact sheet describes the distribution of this pest, ways to distinguish it from other similar corn ear pests, its life cycle, the damage it causes, and some strategies for management. Written by David Owens, Gregg S. Nuessly, Robert Beiriger, and Nicholas Larsen, and published by the Department of Entomology and Nematology, August 2016.